Acculturation patterns resulting from the intersection of globalisation and national identity in South Africa and their impact on the consumption of luxury skincare amongst women - Chipp, Kerry (University of Pretoria, 2017)
Mini Dissertation (MBA)--University of Pretoria, 2017.